Mission-oriented innovation policy: From ambition to successful implementation; Missionsorientierte Innovationspolitik. Von der Ambition zur erfolgreichen Umsetzung - Ralf Lindner; Jakob Edler; Miriam Hufnagl; Simone Kimpeler; Henning Kroll; Florian Roth; Florian Wittmann; Merve Yorulmaz (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2021)
The major problems facing society, the so-called »Grand Challenges«, call for mission-oriented innovation policy. We aim to make a conceptual contribution here and identify the main components.
urn:nbn:de:0011-n-6486390
Keywords: 330